Iran health system reform plan methodology. - H Esmailzadeh; F Rajabi; N Rostamigooran; R Majdzadeh (Tehran University of Medical Sciences, 2013)
The Ministry of Health and Medical Education of Iran, along with the country movement towards achievements of Iran's Vision 2025 put compilation of the health system reform plan on its agenda. In this article, we are trying to show the method we used for developing this plan and how this method considered the general condition of the country along with maintaining the standards of scientific and technical programs. All steps of this planning are described in the paper and finally we discuss the techniques and the appropriateness of the method compare with the experience of the other countries.